DOI: 10.32469/10355/85818
|View full text |Cite
|
Sign up to set email alerts
|

Teacher collaboration and instructional program coherence across the transition to high school

Abstract: This study explores to what extent principals perceive instructional program coherence (IPC) and vertical collaboration occur in high schools and their mid-level feeder schools. It also measures IPC and its five components' association with different measures of student achievement. The study took place in the state of Missouri, and 312 principals of high schools with separate feeder middle schools were invited to participate. Electronic and paper surveys as well as public data were collected and analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…Likewise, we identified only seven papers that even peripherally examine the relationship between measures of system coherence and student outcomes (Atchison et al, 2022;Furtak, Circi, and Heredia, 2018;Moon, Camburn, and Sebastian, 2022;Newmann et al, 2011;Polikoff and Porter, 2014;Sebastian and Allensworth, 2012;Thompson, 2021; see Table 2). In one such study, Newmann and colleagues (2001) identified a strong, positive relationship between school-level increases in coherence as reported by teachers and student achievement.…”
Section: Findings Relating Coherence To Instruction or Learning Are L...mentioning
confidence: 99%
“…Likewise, we identified only seven papers that even peripherally examine the relationship between measures of system coherence and student outcomes (Atchison et al, 2022;Furtak, Circi, and Heredia, 2018;Moon, Camburn, and Sebastian, 2022;Newmann et al, 2011;Polikoff and Porter, 2014;Sebastian and Allensworth, 2012;Thompson, 2021; see Table 2). In one such study, Newmann and colleagues (2001) identified a strong, positive relationship between school-level increases in coherence as reported by teachers and student achievement.…”
Section: Findings Relating Coherence To Instruction or Learning Are L...mentioning
confidence: 99%